Strategi Peningkatan Nilai Perusahaan: Analisis Keputusan Investasi dan Pendanaan dengan Intervensi Kebijakan Dividen - Yuliyanti, Eka; Kartika, Andi; Mustahidda, Rahmania; Fadhila, Zati Rizka (EconBank: Journal of Economics and Banking, 2024)
This study aims to analyze strategies to increase firm value through investment and funding decisions with dividend policy intervention. This type of research falls into the causal associative category. The data sources in this study include all companies in the energy sector listed on the Indonesia Stock Exchange in the period 2019 to 2023. The sampling method applied is purposive sampling. The total population in this study was 145 companies, and of these, a sample of 29 companies was taken. The approach applied to analyze the data is SEM-PLS. The results of the study indicate that investment decisions have a positive relationship with dividend policy, although not statistically significant. Funding decisions have a negative and significant effect on dividend policy. Investment decisions are shown to have a significant negative relationship with firm value. Funding decisions do not show a significant effect on firm value. Dividend policy is proven to have a positive and significant effect on firm value. Dividend policy is able to mediate the effect of funding decisions on firm value. However, dividend policy is not able to mediate the effect of investment decisions on firm value